Response to Palm Plantation Waste Fermentation as Forage and its Relation to the Increase in Buffalo Weight Gain - Harly, Resolinda; Siswati, Latifah; Mulyani, Sri (Pakistan Journal of Nutrition, 2018)
Background and Objective: Ruminant cattle such as buffalo need green plants as their main food source to support life and growth. Green plants are usually taken from local grasslands as well as farming waste. However, the current situation indicates that the green plant supply has decreased, especially during long droughts. Palm oil plantations play a primary role in supporting the green plant supply for the cattle as they produce industrial and agricultural waste. For individual agriculture, green plants that can be consumed by the cattle include midribs and the palm leaves. Palm oil agricultural waste contains high amounts of crude fiber, so fermentation and aeration are important to improve the quality of agricultural waste as well as green plants that contain high amounts of crude fiber. This work discusses the capability of buffalo to process palm oil waste, especially the palm leaves without sticks, that has been fermented and its relation to the increase in buffalo weight. The objective of this research was to explain the ability of buffalo to digest fermented palm leaves, which consistently increase the daily weigh. Materials and Methods: This field research was conducted in Lubuk Basung, Distric Agam from April-May, 2017. Daily weight gain of buffalos was measured and amount of fodder was calculated. Results: The results show that the fermentation of palm leaves without sticks may increase the daily weight gain by approximately 0.89±0.33 kg/buffalo/day, while the consumption of fodder is approximately 18.9±0.74 kg/buffalo/day. Conclusion: Palm waste as forage exhibits a positive impact on the daily weight gain of buffalo.